Análisis de la gestión de responsabilidad social universitaria, aplicado a las Carreras de la Universidad Politécnica Salesiana - Campus Sur en la Administración zonal Quitumbe de la ciudad de Quito - Morán Vega, Susana Elizabeth (2014)
This research evaluates the university social responsibility managed by academic careers that make up the south campus of Quito headquarters of the Salesian Polytechnic University and its application in society comprising Quitumbe Zonal Administration. From the restructuring of the Organic Law on Higher Education in Ecuador, university management using criteria for assessing the training of professionals, with all interactions involved in this process is evaluated.